The Effect of Lactobacillus Consumption on Human Blood Pressure: a Systematic Review and Meta-Analysis of Randomized Controlled Trials. (November 2020) - Liu, Jinshu; Zhang, Dan; Guo, Yingze; Cai, Hongwei; Liu, Keyuan; He, Yayu; Liu, Yumo; Guo, Lirong
Highlights: Lactobacillus consumption significantly reduced SBP and DBP. The effective daily dose of Lactobacillus in BP reduction was >5 × 10 9 CFU. A greater reduction was found in BP when participants received the Lactobacillus in capsule form. The BP-lowering effect of Lactobacillus consumption was more significant in T2DM, Asian and borderline hypertension individuals. Abstract: Objectives: Previous clinical studies have shown controversial results regarding the effect of Lactobacillus supplementation on blood pressure (BP). The purpose of this systematic review and meta-analysis is to examine the effect of Lactobacillus consumption on BP. Methods: Eligible randomized controlled trials (RCTs) were searched from five electronic databases until May 2020. In total, 18 studies were included in our meta-analysis. Quality of the selected studies was assessed, and a random-effects model was used to calculate the overall effect sizes of weighted mean differences (WMD). This systematic review was registered in PROSPERO with the number: CRD42019139294. Results: Lactobacillus consumption significantly reduced systolic blood pressure (SBP) by −2.74 mmHg (95% confidence interval, −4.96 to −0.51) and diastolic blood pressure (DBP) by −1.50 mmHg (95% confidence interval, −2.44 to −0.56) when comparing with the control group. Subgroup analysis showed that type 2 diabetes mellitus (T2DM) patients, Asian individuals, or borderline hypertension participants were more sensitive to daily consumption of Lactobacillus . And the effect of Lactobacillus on BP-reduction was more significant in capsule form, with the dose was above 5 × 10 9 colony-forming unit (CFU)/day or lasted for more than 8 weeks. Conclusions: Our present study suggests that Lactobacillus consumption in capsule form when the daily dose is above 5 × 10 9 CFU for more than 8 weeks can decrease SBP or DBP in T2DM patients, borderline hypertension participants or Asian individuals.